PENGARUH INFORMASI FUNDAMENTAL PADA NILAI INTRINSIK SAHAM DENGAN PENDEKATAN PRICE EARNING RATIO DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Shinta Anggraini; Achmad Tjahjono (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
Stocks are an interesting instrumen for investor to invesment. By making a purchase of stock, investor expect to get provit form capital gain and dividenalthough must get risk.In the stock investment process, investors do an evaluation and analysis of factors that can affect the intrinsic value of the company’s stockprice using one of the fundamental analysis method with Price Earning Ratio (PER) approach. The purpose of this study is to obtain empirical evidence of the influence of firm size, sales growth, dividen police and value of the rupiah exchange rate on intrinsic value of stock. The populationof this study banking companies listed on the Indonesian Stock Exchange period 2011-2015. This study uses secondary data taken from the annual report of banking companies during the year 2011-2015 listed on the Indonesia Stock Exchange. The number of samples of this study as many 7 banking companies with total of 35 data. This research method is quantitative research. The results of this study indicate that firm size variables have a significant positive effect on intrinsic value of stock, while sales growth, dividend policy and rupiah exchange rate do not influence intrinsic value of stock with price earning ratio approach.